Polyneuritis cranialis: A rare variant of Guillain Barré syndrome - Maharjan, Elina; Pandey, Namrata; Maharjan, Sunil; Acharya, Niranjan; Kansakar, Rochak (Journal of Gandaki Medical College-Nepal, 2024)
Polyneuritis cranialis is a rare variant of Guillain-Barré Syndrome. We hereby report a thirty-year-old male with symptoms of headache, vomiting, and blurred vision. Polyneuritis Cranialis was confirmed after considering clinical findings, examinations, and laboratory tests while ruling out other differentials. Intravenous Immunoglobulin treatment over five days led to gradual improvement and discharge on the twentieth day post-admission.